Mendalami Dasar-Dasar dalam Pengambilan Pose pada Pemotretan Model - Gunawan, Agnes Paulina (Bina Nusantara University, 2013)
There are many activities and numerous objects in this universe, which make them interesting for photographers to explore as their masterpiece. One of the things that has been enjoyed and is always developing over time is the use of human as an object, whether as a candid photography or as a posing model in accordance to photographer's concept and theme. Using human being as an object is always popular among beginners and professional photographers. Even nowadays people often hold photo shoot as a media in many social network sites. And so if they understand the simple theories in basic knowledge of using human object, the results will be maximized, and of course, much more interesting. The more a photographer does his job, the better his experience is, and his work will develop. Thus, it makes him more alert to the situation and character of a model, which will then become more observant in predicting their outcome in photography.